2015
DOI: 10.1002/jmr.2487
|View full text |Cite
|
Sign up to set email alerts
|

Lectins as probes for assessing the accessibility of N‐linked glycans in relation to the conformational changes of fibronectin

Abstract: Fibronectin, a ≈ 450-kDa protein with 4-9% (w/w) glycosylation, is a key component of extracellular matrices and has a high conformational lability regarding its functions. However, the accessibility and the role of glycosylated moieties associated with the conformational changes of fibronectin are poorly understood. Using lectins as probes, we developed an approach comprising dynamic light scattering, turbidimetry measurements, and isothermal titration calorimetry to assess the accessibility of glycosylated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…The binding activity of human Vn has been found to increase under heating. Our group has recently described the effect of thermal treatment on the glycan accessibility of human plasma Fn, another adhesive glycoprotein, using the mannose‐binding ConA lectin . ConA is widely used as molecular probe in glyco‐biotechnology, and our present study demonstrated distinct ConA binding patterns according to Vn origin.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The binding activity of human Vn has been found to increase under heating. Our group has recently described the effect of thermal treatment on the glycan accessibility of human plasma Fn, another adhesive glycoprotein, using the mannose‐binding ConA lectin . ConA is widely used as molecular probe in glyco‐biotechnology, and our present study demonstrated distinct ConA binding patterns according to Vn origin.…”
Section: Resultssupporting
confidence: 56%
“…It belongs to the calcium‐dependent (C‐type) lectin family, which shares structural and functional homologies with animal C‐type lectins as blood plasma mannan binding proteins . ConA is one of the most widely studied lectins due to its wide range biological functions, such as immune‐stimulating activity, and to its biotechnological applications to characterize glycoproteins from clinical specimens, as shown by our group …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Pro–His–Ser–Arg–Asn is an amino acid sequence, found in fibronectin, whose activation results in the enhancement of signaling responses that initiate stem cell recruitment . Despite these merits, ECM proteins have several major shortcomings that limit their clinical use, such as potential risk of pathogen transmission, unsolicited adverse immune response (against cadaveric or xenogenic proteins), and bioactivity loss owing to conformational changes during conjugation to scaffolds …”
Section: Cell Adhesion Molecules For Surface Modificationmentioning
confidence: 99%
“…An important role in understanding biomolecule interaction and in the study of extracellular membranes is played by glycoprotein association with lectins and integrins [82]. In this area, two groups have developed FBG-based biosensors exploiting the interaction between concanavalin A (ConA) and mannose-functionalized dendrimers [32] and between fibronectin and fibroblast cells to study the cell response to stimuli [36].…”
Section: Ofg-based Biosensing Based On Other Bresmentioning
confidence: 99%